2007
DOI: 10.12927/hcpol.2007.19397
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Surgeon Views on Maximum Acceptable Waiting Times for Joint Replacement

Abstract: Objective: To assess patient and surgeon views on maximum acceptable waiting times (MAWT) for hip and knee replacement, their determinants and their relationship to levels of urgency based on the Western Canada Waiting List Priority Criteria Score (PCS). Methods: At the decision date for surgery, orthopaedic surgeons assessed consecutive patients with the PCS and MAWT. Patients were surveyed 3-12 months post-surgery for MAWT and potential determinants. Results: The patient sample of 208 was 56% female, mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In the postsurgery group, the time interval between surgery and the survey had no significant effect on MAWT, consistent with previous testing. 14 In multiple regression analysis, adjusting for sex and actual WT, variables significantly associated with a longer MAWT were younger age, group (waiting), a longer self-reported WT, better EQ-5D index, an acceptable WT, a perceived fairness and a view that others worse off should have priority (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the postsurgery group, the time interval between surgery and the survey had no significant effect on MAWT, consistent with previous testing. 14 In multiple regression analysis, adjusting for sex and actual WT, variables significantly associated with a longer MAWT were younger age, group (waiting), a longer self-reported WT, better EQ-5D index, an acceptable WT, a perceived fairness and a view that others worse off should have priority (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire was designed to assess patients' perspectives on waiting for surgery and had been previously tested in postsurgery patients. 14 For the current study, items were adapted for the waiting group questionnaire and both questionnaires were evaluated for interpretability and comprehensiveness by participants of four focus groups, randomly selected from the Registry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaire items were previously tested in a consecutive group of post-surgery patients [27]. For the current study, items were adapted for the waiting group questionnaire and both questionnaires were reviewed for clarity, interpretability, and comprehensiveness by participants of four focus groups, randomly selected from the Saskatchewan Surgical Registry.…”
mentioning
confidence: 99%
“…There has been some investigation of patient perceptions of waiting time for THR and TKR 2 ISRN Public Health surgery in the Canadian health system-a system which, like Australia, is supported by a taxation-based funding structure. Individuals in these studies reported maximum acceptable waiting periods ranging from 12 (SD 8.35) to 18 (SD 11.0) weeks [15,16]. No similar information is available within the Australian population.…”
Section: Introductionmentioning
confidence: 99%